A Versatile Internet-Accessible Electronics Workbench with Troubleshooting Capabilities - Soumare, Hamidou; Shroff, Rahul; Hardison, James L; del Alamo, Jesus A; Harward, V Judson; Bailey, Philip H; DeLong, Kirky K (International Journal of Online and Biomedical Engineering (iJOE), 2009)
The MIT iLab Project was established to expand the range of laboratory experiences available to students in science and engineering education. iLabs are online laboratories that enable students to conduct real experiments remotely. Recently, the iLab Project has focused on building remote laboratories around the NI-ELVIS platform, an all-in-one electronics workbench. This paper will detail our recent efforts in expanding the capabilities of ELVIS-based iLabs by enabling students to test and debug digital and analog circuits. This work will enable students to perform remote experiments characterizing digital logic elements. By merging switching capabilities with the Digital Multimeter available on the ELVIS, students will have the ability to examine and troubleshoot circuits. These added capabilities will provide educators and students with unparalleled flexibility and significantly enrich the remote laboratory experience.